Therapeutic lipid target achievements among high and highest risk patients: results from the CEPHEUS study in the Arabian Gulf. (December 2014) - Al-Rasadi, Khalid; Al-Zakwani, Ibrahim; Al Mahmeed, Wael; Arafah, Mohamed; Al-Hinai, Ali T.; Shehab, Abdullah; Al Tamimi, Omer; Alawadhi, Mahmoud
Abstract Objective: To determine lipid target achievements of low-density lipoprotein cholesterol (LDL-C), non-high density lipoprotein cholesterol (non-HDL-C) and apolipoprotein B (apo B) in the Centralized Pan-Middle East Survey on the undertreatment of hypercholesterolemia (CEPHEUS) in Arabian Gulf States patients with high and highest risk according to the joint Consensus Statement of the American Diabetes Association (ADA) and American College of Cardiology Foundation (ACC). Methods: CEPHEUS was conducted in patients (≥18 years of age) in six Middle Eastern countries between November 2009 and July 2010 on lipid lowering drugs (LLDs). Serum samples collected included total cholesterol (TC), LDL-C, HDL-C, triglycerides (TGs), apo B, and apolipoprotein A1 (apo A1). Results: The overall mean age of the cohort (n = 5275) was 56 ± 13 years, 58% (n = 3060) were male and 69% (n = 3635) were highest risk. LDL-C target was achieved in 25%, non-HDL-C in 36% and apo B in 38% of patients in the highest risk cohort compared with LDL-C 46%, non-HDL-C 58% and apo B 51% in the high risk group. In patients with TGs ≥2.2 mmol/L, LDL-C target was achieved in 16% and apo B in 15% of patients in the highest risk group compared with LDL-C 32% and apo B 22% in the high risk cohort. Conclusion: Despite being on LLDs, a large proportion of high and highest risk patients in the Arabian Gulf are not at recommended lipid targets and remain at a substantial residual risk for cardiovascular diseases. Apo B may be used as an additional target in patients with triglycerides ≥2.2 mmol/L. The findings should be interpreted in light of the study's limitations.